Search for meteoritic GEMS II: Comparison of inclusions in amorphous silicates from the Paris chondrite and from anhydrous chondritic interplanetary dust particles. (1st October 2021) - Villalon, K.L.; Ohtaki, K.K.; Bradley, J.P.; Ishii, H.A.; Davis, A.M.; Stephan, T.
Abstract: Amorphous silicates containing abundant nano-inclusions have been reported in the Paris CM chondrite (Leroux et al., 2015). They have chemical and morphological similarities to glass with embedded metal and sulfides (GEMS) found in interplanetary dust particles (IDPs) and micrometeorites believed to originate from comets. We used scanning transmission electron microscopy (STEM) with energy-dispersive X-ray spectroscopy (EDS) and nanodiffraction to study the chemistry and mineralogy of these inclusions in order to understand the origin of the GEMS-like material in Paris and its possible relationships to other materials found in primitive chondritic materials including IDP GEMS. EDS and diffraction analyses indicate compositional and mineralogical differences between the nanophase inclusions in cometary GEMS and Paris GEMS-like material. Metal inclusions are notably absent within Paris amorphous silicate. Ni-rich sulfides, including pentlandite, are common in even the least altered matrix material of Paris, while they are absent in GEMS-bearing IDPs and Ultracarbonaceous Antarctic Micrometeorites (UCAMMs). From examination of the inclusions, we cannot yet confirm or refute the possibility that GEMS-like material in Paris is related to cometary GEMS. The distinct compositions and mineralogy of the Paris material may be due to aqueous alteration of cometary GEMS precursors, but they may also denote an independent origin for meteoritic GEMS-like assemblages.